2021
DOI: 10.3808/jeil.202100058
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Impact Analysis of Dispersants and Dispersed Oil: An Overview

Abstract: Soaring oil demand, as a result of industrial development, boosts oil exploration and production activities at sea, even into deeper and icier waters. The transportation of the oils, as well as the potential spill accidents and associated pollutions are thus increased. There is an urgent call for contingency planning with effective and eco-friendly oil spill cleanup responses. Dispersant applications can facilitate the breaking up of oil slicks into small oil droplets, allowing their rapid dispersion, dissolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Moreover, MPs incorporated with halogenated contaminants posed toxic effects on the European seabass [12]. Moreover, oil spills were accidentally occurred during offshore oil production and have raised a global concern due to their severe negative impacts on ocean sustainability [13,14]. Recent studies reported the abundance of MPs in oil-contaminated regions, such as the Persian Gulf [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MPs incorporated with halogenated contaminants posed toxic effects on the European seabass [12]. Moreover, oil spills were accidentally occurred during offshore oil production and have raised a global concern due to their severe negative impacts on ocean sustainability [13,14]. Recent studies reported the abundance of MPs in oil-contaminated regions, such as the Persian Gulf [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%